2016
DOI: 10.1186/s12969-016-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with Juvenile Idiopathic Arthritis: relationship to perceived health, physical health, self-efficacy, and participation

Abstract: BackgroundFatigue is common in patients with JIA and affects daily life negatively. We assessed the presence and severity of fatigue in patients with JIA, including factors presumed associated with fatigue (e.g., disease activity, disability, pain, physical activity, exercise capacity, and self-efficacy), and whether fatigue is related to participation in physical education classes, school attendance, and sports frequency.MethodsThe current study used baseline data of 80 patients with JIA (age 8–13) who partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 40 publications
(53 reference statements)
9
36
3
1
Order By: Relevance
“…These challenges can include both somatic and psychosocial aspects 2 3. Fatigue is often one such challenge and can have a significant impact on the well-being and participation in daily life of the child or adolescent and his or her family 4–6…”
Section: Introductionmentioning
confidence: 99%
“…These challenges can include both somatic and psychosocial aspects 2 3. Fatigue is often one such challenge and can have a significant impact on the well-being and participation in daily life of the child or adolescent and his or her family 4–6…”
Section: Introductionmentioning
confidence: 99%
“…In a trajectory analysis, Shiff et al reported that disease activity only accounted for a small portion of variability in pain severity in children with JIA [18]. The same picture emerged for fatigue: although fatigue is a prominent feature in many JIA patients, disease activity seems not to be directly related to it [19][20][21]. Interestingly, Ringold et al hypothesized that pain may be an intermediate link between disease activity and fatigue [21].…”
mentioning
confidence: 99%
“…Notably, participants reported minor JIA symptoms and a good overall well‐being. Overall, there is limited information available from other studies that examined the relationship between school attendance and mood/stiffness , fatigue , and tender joints .…”
Section: Discussionmentioning
confidence: 99%